Lyme Borreliosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Even though as far back as the last century isolated reports of the relevant literature talk about the relationship between tick bites and clinical manifestations involving the skin, the articulations and other organs, only in the last 10 years the causative role of Borrelia burgdorferi in the etiology of Lyme disease has been fully elucidated. (...).